Effectiveness of Using Blended Learning Media in Christian Religious Education - Bonar Dominggos Simanjuntak; Resiani Simamora; Daniel Ricel Fredik Polii; Darmin Usman Zega (Asian Journal of Philosophy and Religion, 2023)
The purpose of this study is to describe the effectiveness of using blended learning through Christian Religious Education. Blended learning is a solution to society's high need for education but is hindered by busyness, time and distance, as well as answering the wishes of some people who still want face-to-face learning. Christian religious education also applies blended learning to free individuals from the shackles of ignorance. Therefore, this research has a background problem, whether blended learning is effectively used in Christian religious education. The method used in this research is a descriptive qualitative method approach. The research process was carried out using library study techniques, namely collecting data, sorting, reading, analyzing and drawing conclusions. This research will produce a description of blended learning effectively used in Christian Religious Education.